1
$\begingroup$

An Even function divided by Odd function is an Odd function,that is a fact. However is there a means to prove this?

$\endgroup$
7
$\begingroup$

Let $h(x)$ be an even function, which means that $h(-x)=h(x)$ and $g(x)$ be an odd function, which means that $g(-x)=-g(x)$.

Let $f(x)=\frac{h(x)}{g(x)}$.

Then, $f(-x)=\frac{h(-x)}{g(-x)}=\frac{h(x)}{-g(x)}=-f(x).$$\text{ }$ $\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\square$

$\endgroup$
0
$\begingroup$

Let $f$ be an odd function : $ f(-x) = - f(x) $ for all $x$. Let $g$ be an even function: $g(-x) = g(x) $ for all $x$. Now, put $h(x) = \frac{ g(x) }{f(x) } $

$$ h(-x) = \frac{ g(-x) }{f(-x) } = \frac{ g(x) }{ - f(x) } = - \frac{ g(x) }{f(x) }= - h(x) $$

Hence, $h$ is odd.

$\endgroup$
  • $\begingroup$ I think you need an equals sign in your last step. $\endgroup$ – Sherlock Holmes Oct 23 '14 at 1:43

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.